Introducing an evidence based medicine course to second year medical students - evaluating its effectiveness and student feedback (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Objectives: To study the effectiveness of Introducing an Evidence Based Medicine (EBM) course in the curriculum of Second Year Medical Students and to obtain their feedback regarding the same.Methods: 66 students consented and participated in the study. EBM was introduced as a series of 6 lectures of different topics including basic biostatistics and framing of clinical question. A couple of hands on sessions regarding efficient searching of Medline for evidence and critical appraisal of research studies were also conducted. As a part of the course students were asked to download an original research article and critically appraise it using a checklist provided to them. Fresno test of competence in EBM was used to assess EBM knowledge and skills before and after the course. Differences between pre and post test scores were statistically analyzed by chi square and Student t-test.Observations: The students showed significant improvement in their post test scores. The student feedback regarding the course was positive and encouraging. 57(86%) of the students felt that the course helped them in the understanding of the principles of EBM and that it also increased their ability to search for new information  more efficiently. 46(70%) of them agreed that EBM should be included in their regular MBBS curriculum.Conclusion: The course was effective in improving the student knowledge and skills regarding EBM. It was also positively accepted by the students and most of them found it to be useful, informative, interesting and relevant.